2010
DOI: 10.2118/122307-pa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flowback Aids: Understanding Their Capillary Pressure and Wetting Properties

Abstract: Summary Flowback aids are usually surfactants or cosolvents added to stimulation treatments to reduce capillary pressure and water blocks. As the stimulated gas reservoirs become tighter, the perceived value of these additives has grown. This value must be balanced with the cost of the additives, which can be significant in slickwater fracturing treatments. There is a range of different flowback additives containing water-wetting nonionic to amphoteric, microemulsion (ME), and oil-wetting compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Gdanski (2007) agrees with this, though he states that some of the negative effects of water saturation, specifically high capillary pressures, often become negligible in permeabilities of 1 mD or more. This is validated in work conducted by Howard et al (2009) where retained permeability of cores greater than 1mD showed no benefit from surfactant or microemulsion usage. While laboratory testing can provide a basis for flowback aid selection, the case histories presented in our paper show that flowback aids giving comparable results in the laboratory may give significantly different results under field application.…”
Section: Introductionsupporting
confidence: 53%
“…Gdanski (2007) agrees with this, though he states that some of the negative effects of water saturation, specifically high capillary pressures, often become negligible in permeabilities of 1 mD or more. This is validated in work conducted by Howard et al (2009) where retained permeability of cores greater than 1mD showed no benefit from surfactant or microemulsion usage. While laboratory testing can provide a basis for flowback aid selection, the case histories presented in our paper show that flowback aids giving comparable results in the laboratory may give significantly different results under field application.…”
Section: Introductionsupporting
confidence: 53%
“…Values of γ S d are consistently lower than the value of γ S LW , which is expected according to eqs. (4) and (8). Furthermore, the analysis clearly shows that shale surface is a weak electron donor and that the tendency to formation of hydrogen bonding is very low, as evidenced by low γ S AB component.…”
Section: Resultsmentioning
confidence: 93%
“…At the same time, γ S AB and γcomponents are much lower than those of quartz, indicating that electron-donor and hydrogen bonding properties of shale surface are much weaker than those of quartz. This suggests that glass or quartz slides may not be completely realistic model substrates for studies of fracturing fluids additives with intended application in shales [8]. In fact, the determined values of surface free energy components of shales are very similar to the surface energy components of some low-rank coals [19], indicating that studies on surfactant interaction with coals should be relevant to shales to a larger extent than studies on glass and quartz.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations